Increasing Brand Awareness of Keka Catering Through Social Media “Instagram” - Kezia Callista (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This creative thesis to solve the problem that KeKa Catering has. KeKa Catering is different with the general catering which serve it daily and has same menu. However, KeKa Catering has different menu which are Banjarmasin’s foods and snacks. Their problem is there is still many people who do not recognize their brand or product. Even though KeKa Catering already has their promotional tool, which is Instagram, but they do not use it properly. That is why developing their Instagram account is the best way. It is because will cost less than marketing booklet and the other tools. There are 12 contents on their Instagram account. The customer of KeKa Catering is around 25 until 35 years old. That is why I use slang or internet word for the choice of language. With Instagram the target customers are broader, and many people will recognize easily.Keywords: brand awareness, catering, social media, Instagram